FILSAFAT IBNU RUSYD HUBUNGAN AKAL DENGAN WAHYU - Kaipal Wahyudi (Indonesian Journal of Islamic and Social Science, 2023)
Ibnu Rushd was an intellectual Muslim who was known as a rational figure in the Islamic tradition. In his understanding he emphasized the importance of reason and logic in understanding religion and that all aspects of religion must be resolved through the power of reason. Ibn Rushd's famous work, "Fasl al-Maqal" emphasizes that logic must be the basis for assessing truth. In this context, Ibn Rushd offers the importance of religious verses with reason and revelation. For him, logic is not only an analytical tool, but also a way to understand revelation in depth. In understanding religion, according to Ibnu Rushd, a person must learn to think logically. Although reason and logic are important aspects in solving occult and complex problems related to religion, Ibn Rushd also incorporates the principle of relationships (ittisal) in his thinking. He tried to find a harmonious relationship between religion and philosophy. According to him, studying philosophy has an important position in understanding the knowledge of God, namely philosophical activities that study and think about everything that exists (al-mawjudat). Ibn Rushd believes that al-mawjudat, as a product of creation, is an indication of the existence of a Creator. The more we understand God's creation, the more perfect our knowledge of Him will be. Therefore, Ibn Rushd encouraged reflection and contemplation about al-mawjudat, and he assumed that studying philosophy was an obligation and command given through revelation. Thus, Ibn Rushd's approach to philosophy emphasizes the importance of combining reason and revelation, where logic is used as an instrument to understand and comprehend religious teachings in more depth